TOPICAL ISSUES OF ANESTHESIOLOGY AND INTENSIVE CARE - Yu. S. Polushin (Вестник анестезиологии и реаниматологии)
In no way questioning the achievements of the Russian anesthesiology and intensive care, the author pays special attention to certain topical issues. From his point of view, these issues point out at the fact that anesthesiology and intensive care system is falling behind healthcare reforming. The author expresses his concerns about the current situation, especially about the growing gap between high requirements to the quality of care provided by anesthesiologists and emergency physicians and constraints interfering with it due to various reasons. The author suggests striving for the division of anesthesiology and intensive care into the relevant levels, elaboration of clear requirements to primary (basic) training of graduates from medical residences and expresses some other opinions. Considering the novelty of his proposals, the author invites to discuss them in the publications of this journal and during the 2nd Congress on Topical Issues of Critical Care Medicine (May 11-14, 2019).